The battle plans in the 17th century on the example of the 'ordres de bataille' album by Eric Dahlbergh. Research model proposal. - Balcerek, Mariusz (Digital Scholarship in the Humanities, 2023)
The article's purpose is to present an original method of analysis of battle plans (orders of battle, battle orders, battle patterns, and battle settings) from the 17th century. We analysed 253 patterns from Eric Dahlbergh's Album, which was a gift for King Charles XI of Sweden. In this text, we will take a look at the settings presented in Dahlbergh's album. We hope that it will allow us to learn about the development process of the 17th-century arrays. What was the typical 17th-century order of battle like? Was it symmetrical or asymmetrical? How many throws and lines did it consist of? What was the ratio of the width to the depth of the army? Was the pattern composed of compact or linear elements? How did the formations (cavalry and infantry) stack up against each other? What was the frequency of intervals and higher tactical units? Thanks to the developed method, we obtained data for many patterns for the first time in history. They made it possible to characterize the patterns accurately and determine the time they changed. It is of paramount importance for the study of the European military in the early modern period.